Undang-Undang Islam di mahkamah-mahkamah syariah di Malaysia - Ahmad Hidayat Buang ([Kuala Lumpur] : Jabatan Syariah dan Undang-Undang, Akademi Pengajian Islam, Universiti Malaya, 1998)
Islamic law applied at religious courts in Malaysia; papers of a seminar.
Includes bibliographical references and indexes.
Keywords: Courts -- Malaysia -- Congresses; Islamic courts -- Malaysia -- Congresses; Civil procedure -- Malaysia -- Congresses; Civil procedure (Islamic law) -- Congresses